1994
DOI: 10.1038/ng0294-152
|View full text |Cite
|
Sign up to set email alerts
|

Instability of short tandem repeats (microsatellites) in human cancers

Abstract: The allele sizes of polymorphic microsatellite repeats in DNA from human cancers were compared to normal DNA from the same patients. In 16 out of 196 paired samples (8%), we found evidence of an extra allele of a different size in the tumour which was not present in the normal DNA. Sequence analysis confirmed that the extra allele originates from the appropriate locus and that the size change is attributable to alteration in the number of repeat units. This form of instability was more common in tri- and tetra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
189
4
4

Year Published

1996
1996
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 361 publications
(214 citation statements)
references
References 19 publications
16
189
4
4
Order By: Relevance
“…Until such uniformity is achieved, direct comparisons of the results obtained by different research groups is impossible and can lead to wildly different estimates of the rate of MSI in a given tumour type Peltomaki et al, 1993;Patel et al, 1994). If the presence of any MSI is assumed to be indicative of an RER+ phenotype, then the rate of RER+ tumours seen in this study was 10.8%, similar to that reported by Wooster et al (1994).…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…Until such uniformity is achieved, direct comparisons of the results obtained by different research groups is impossible and can lead to wildly different estimates of the rate of MSI in a given tumour type Peltomaki et al, 1993;Patel et al, 1994). If the presence of any MSI is assumed to be indicative of an RER+ phenotype, then the rate of RER+ tumours seen in this study was 10.8%, similar to that reported by Wooster et al (1994).…”
Section: Resultssupporting
confidence: 88%
“…Size instability in microsatellite DNA is associated with certain neurological conditions (Willems, 1994) and has been demonstrated more recently in a variety of malignant neoplasms (e.g. Han et al, 1993;Peltomaki et al, 1993;Horii et al, 1994;Wooster et al, 1994). There is in vitro evidence that cells with defective MMR genes carry a high frequency of errors in microsatellite sequences (Liu et al, 1995).…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…osteosarcoma, Table I) and none showed MI. However, as a small proportion of soft-tissue sarcomas exhibited a low degree of MI in a previous study (Wooster et al, 1994), it is still possible that microsatellite instability could be detected in a distinct subgroup of bone tumours, at least with a low degree. Furthermore, preliminary results of mice deficient for PMS2 or MSH2 have shown that these animals may be susceptible to developing sarcomas (Baker et al, 1995;de Wind et al, 1995).…”
Section: Discussionmentioning
confidence: 80%
“…So far mesenchymal tumours have been screened for RER in only one study, in which two of 18 soft-tissue sarcomas exhibited instability with one repeat (Wooster et al, 1994). In a study of loss of heterozygosity (LOH) in chondrosarcomas with markers linked to multiple hereditary exostoses loci no evidence of MI was seen (Raskind et al, 1995).…”
mentioning
confidence: 99%